2022
DOI: 10.1073/pnas.2201927119
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic membranes participate in hepatitis B virus nucleocapsid assembly, precore and core protein trafficking, and viral release

Abstract: Hepatitis B virus (HBV) DNA replication takes place inside the viral core particle and is dependent on autophagy. Here we show that HBV core particles are associated with autophagosomes and phagophores in cells that productively replicate HBV. These autophagic membrane-associated core particles contain almost entirely the hypophosphorylated core protein and are DNA replication competent. As the hyperphosphorylated core protein can be localized to phagophores and the dephosphorylation of the core protein is ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…Interestingly, a portion of phosphorylated precore proteins, P-p25 and P-p22, were also associated with membrane compartments in the absence of other HBV proteins ( Fig. 2F ), possibly with autophagosomes, as shown recently ( 36 ). The presence of a small amount of p22 in the supernatant of overexpressing cells as a low-density entity ( Fig.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Interestingly, a portion of phosphorylated precore proteins, P-p25 and P-p22, were also associated with membrane compartments in the absence of other HBV proteins ( Fig. 2F ), possibly with autophagosomes, as shown recently ( 36 ). The presence of a small amount of p22 in the supernatant of overexpressing cells as a low-density entity ( Fig.…”
Section: Discussionsupporting
confidence: 82%
“…2F ). It is likely that some P-p22 and P-p25, phosphorylated in the cytosol, were associated with autophagosomes, as was recently reported ( 36 ). Altogether, we detected phosphorylated and unphosphorylated p22 and p25 in both HBV-infected PHHs and precore-transfected hepatoma cells.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Studies have shown that some viruses can use autophagy for self-protection and proliferation, such as autophagy membrane that participates in the nucleocapsid assembly and the release of hepatitis B virus. [79] The autophagy induced by poliovirus can increase the viral load of fibroblasts. [80] Because of this characteristic, autophagy has become one of the important mechanisms for studying the entry of pathogens into the host.…”
Section: Autophagymentioning
confidence: 99%
“…8 HBV can exploit mitochondria damage-induced autophagy to facilitate its replication and secretion. 20,36 Host hepatocytes catabolize glucose, amino acids, and free fatty acids through autophagy, thereby providing energy and substrates for HBV replication and secretion.…”
Section: Long-term Antiviral Therapy Improves Lipid Metabolism and Re...mentioning
confidence: 99%